The Mammals of Iona National Park and surrounding areas, Namibe province, southwestern Angola: a preliminary checklist - Freixial, Catarina Laia Franco Albino (2021)
Angola has 14 protected areas throughout the country. Iona National Park is one, but due to the civil war few studies about the mammals were conducted here. This study aims to present a first preliminary checklist of the mammal fauna of this park and its surroundings. For this purpose, recent observation data (based on camera traps, opportunistic observations and records of reliable sources) and historical data (available in bibliography, museum collections and grey literature) were compiled and critically reviewed. A total of 14 orders, 37 families and 120 species were recorded for the study area. Of these, 26 species have recent records, while the remaining 94 only have historical records (where 38 are presented as potential species from the park). New data was obtained and species with no historical records inside Iona National Park were recorded, such as aardvark (Orycteropus afer), zorilla (Ictonyx striatus) and ground pangolin (Smutsia temminckii); Os Mamíferos do Parque Nacional do Iona e áreas circundantes, Província do Namibe, sudoeste Angola: uma lista preliminar Resumo: Angola tem 14 áreas protegidas ao logo do país. O Parque Nacional do Iona é uma delas, mas, devido à guerra civil, poucos estudos sobre mamíferos foram realizados aqui. Este estudo tem como objetivo apresentar a primeira lista de espécies de mamíferos deste parque e áreas circundantes. Para isso, foram compilados e criticamente revistos dados recentes (baseados em foto-armadilhagem, observações diretas e registos de fontes de confiança) e históricos (disponíveis em bibliografia, coleções de museus e literatura). Um total de 14 ordens, 37 famílias e 120 espécies foram registadas para esta área. Destas, 26 espécies têm registos recentes, enquanto as restantes 94 apenas têm registos históricos (onde 38 são apresentadas como potenciais espécies do parque). Novos dados foram obtidos e espécies sem dados históricos foram registados dentro do Parque Nacional do Iona, como o porco-formigueiro (Orycteropus afer), o zorilla (Ictonyx striatus) e o pangolim terrestre (Smutsia temminckii).